A Sudy of the Occupational Safety and Health Management System (SMK3) in Construction Companies (Case Study: Occupational of the Viar or TosaShowroom Building): Kajian Sistem Manajemen Keselamatam dan Kesehatan Kerja (SMK3) pada Perusahaan Konsruksi Bangunan (Studi Kasus: K3 Pembangunan Gedung Showroom Viar) - Maulidya Octaviani Bustamin; Wisnu Abiarto Nugroho; Petrus Para Mite (Universitas Negeri Surabaya, 2026)
This study aims to examine the occupational safety and health (OSH) management system in a construction company, specifically in the Viar or Tosa showroom construction project. It also analyzes workplace accident prevention efforts and the impact of occupational health on work quality. The study employs an observational approach with a descriptive method, while data were analyzed quantitatively using SPSS software. The findings reveal that most workers (92.3%) understood the implementation of the OSH management system, supported by the availability of personal protective equipment (PPE) such as helmets, vests, gloves, and safety shoes. In terms of accident prevention, 88.4% of workers were involved in planning OSH programs, reflecting the company’s commitment to workplace safety. The study further shows that all workers consistently applied the use of PPE during construction activities. Moreover, occupational health practices were found to have a significant influence on work quality, as the majority of workers recognized the importance of the OSH management system in ensuring safety and improving productivity.